zeta-COP, a subunit of coatomer, is required for COP-coated vesicle assembly (The Rockefeller University Press, 1993)
cDNA encoding the 20-kD subunit of coatomer, zeta-COP, predicts a protein of 177-amino acid residues, similar in sequence to AP17 and AP19, subunits of the clathrin adaptor complexes. Polyclonal antibody directed to zeta-COP blocks the binding of coatomer to Golgi membranes and prevents the assembly of COP-coated vesicles on Golgi cisternae. Unlike other coatomer subunits (beta-, beta'-, gamma-, and epsilon- COP), zeta-COP exists in both coatomer bound and free pools.